2008
DOI: 10.1159/000151249
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Non-Erosive Reflux Disease

Abstract: Non-erosive reflux disease (NERD) is a relatively new entity, the definition of which has been evolving and involves the use of symptoms, endoscopy, and objective evidence of reflux or reflux-related damage. The closest entity to NERD that is examined by available epidemiologic studies is defined by the presence of gastroesophageal reflux disease (GERD) symptoms in the absence of esophageal erosions or Barrett’s esophagus. In this review, I identified two population-based studies, one non-community study, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
3
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 23 publications
5
53
3
1
Order By: Relevance
“…This may be attributed to the difference in diagnostic criteria for NERD and FH. Unlike our results, previous observations showed that NERD was associated with younger age, female sex, and psychological comorbidities than ERD [17]. In those observations, the criteria used were different from the Rome III criteria, where NERD was simply defined by the presence of GERD symptoms in the absence of esophageal erosions or Barrett’s esophagus.…”
Section: Discussioncontrasting
confidence: 91%
“…This may be attributed to the difference in diagnostic criteria for NERD and FH. Unlike our results, previous observations showed that NERD was associated with younger age, female sex, and psychological comorbidities than ERD [17]. In those observations, the criteria used were different from the Rome III criteria, where NERD was simply defined by the presence of GERD symptoms in the absence of esophageal erosions or Barrett’s esophagus.…”
Section: Discussioncontrasting
confidence: 91%
“…NERD is probably increasing at least as fast as its ‘parent’ GERD, though it was appreciated that there was little direct evidence to support this assertion [10]. The increase in GERD parallels the increase in obesity in developed nations [11], but the group just failed to support the statement that BMI is contributing to an increase in NERD, principally due to a paucity of research addressing this issue.…”
Section: Clinical Features Of Nerdmentioning
confidence: 99%
“…It has been reported that a significant proportion (up to 75%) of patients with GERD in this region falls under the ''endoscopy-negative'' or non-erosive reflux disease (NERD) group [2]. Although patients with erosive reflux disease (ERD) and NERD are often regarded as part of the spectrum of the same disease, they are different in many ways and are considered by some as different disease entities [3].…”
Section: Introductionmentioning
confidence: 99%